2014
DOI: 10.1002/bsl.2147
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Gender Differences in Jurors' Reactions to Child Sexual Assault Cases

Abstract: In three experiments, we investigated the influence of juror, victim, and case factors on mock jurors' decisions in several types of child sexual assault cases (incest, day care, stranger abduction, and teacher-perpetrated abuse). We also validated and tested the ability of several scales measuring empathy for child victims, children's believability, and opposition to adult/child sex, to mediate the effect of jurors' gender on case judgments. Supporting a theoretical model derived from research on the perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 73 publications
(94 reference statements)
7
44
1
Order By: Relevance
“…Our finding that women perceived the child victim to be more accurate, and the defendant to be more guilty and likely to have sexually abused children, than male participants is consistent with the robust juror gender effect documented in the mock jury literature for child sexual abuse cases (Bottoms et al, ; Golding et al, ). Although our study does not shed light on why these differences emerged, recent research by Bottoms and colleagues () has shown that, compared with men, women are more empathic toward child victims, more opposed to adult/child sex, more pro‐women, and more inclined to believe children generally. They also found that the observed differences in empathy and attitudes generally mediated the juror gender effect.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Our finding that women perceived the child victim to be more accurate, and the defendant to be more guilty and likely to have sexually abused children, than male participants is consistent with the robust juror gender effect documented in the mock jury literature for child sexual abuse cases (Bottoms et al, ; Golding et al, ). Although our study does not shed light on why these differences emerged, recent research by Bottoms and colleagues () has shown that, compared with men, women are more empathic toward child victims, more opposed to adult/child sex, more pro‐women, and more inclined to believe children generally. They also found that the observed differences in empathy and attitudes generally mediated the juror gender effect.…”
Section: Discussioncontrasting
confidence: 69%
“…Yet, similarly to the perceived fairness of alternative testimony procedures, the exact nature and pervasiveness of the juror gender effect is moderated by the specific dependent measures that researchers examine (perceptions of child victim and defendant versus verdict). Summing up this sizeable body of research, Bottoms and colleagues ( concluded that “on average, women are often more likely than men to render a guilty verdict and/or to favor the prosecution in terms of victim and defendant credibility (believability) judgments, victim and witness responsibility judgments” (p. 511). They also noted the juror gender effect extends beyond the jury simulation paradigm per se to some (but not all) studies in which participants read brief vignettes detailing child sexual abuse and then judged abuse seriousness and party blameworthiness.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a brief review was conducted of the 17 studies which failed to meet this review's inclusion criteria due to recruiting participants from outside of England and Wales (eg France, America and Australia). This revealed various factors to influence perceptions towards CSA victims, such as type of abuse (eg Bornstein, Kaplan, & Andrea, 2007), respondent gender (Castelli, Goodman, & Ghetti, 2005), interview style (Castelli et al, 2005) and victim age (Bottoms et al, 2014;Tabak & Klettke, 2014). Whilst this indicates similarities, further research is recommended to ensure conclusions are based on a comprehensive search.…”
Section: Further Researchmentioning
confidence: 89%
“…The finding that females (vs. male) participants ascribed higher credibility to the alleged female child victim, and believed less in the male suspect is consistent with the study by Schmidt and Brigham (), who also identified this pattern, in a CSA mock‐trial. This finding adds to the body of research showing that males and females differ in their tendency to believe in children's sexual abuse testimonies (Bottoms et al ., ; McCauley & Parker, ; O'Donohue et al ., ; O'Donohue & O'Hare, ). Females stating higher belief in children's testimonies have been suggested to be an effect of gender‐based attitude differences.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another factor that may affect the perceived credibility of CSA claims is the gender of the individual making the credibility judgment. A number of studies have found that females are more inclined to believe that children's claims of CSA are true than are males (Bottoms, Peter‐Hagene, Stevenson et al ., ; McCauley & Parker, ; O'Donohue, Elliott, Nickerson & Valentine, ; O'Donohue & O'Hare, ). A recent study by Bottoms and colleagues () explored and found that this gender bias in credibility judgements was mediated by the fact that females tended to make more pro‐child victim judgements and be more empathic towards child victims than males.…”
Section: Introductionmentioning
confidence: 99%